Determinantes del nivel de educación adquirido por una persona en el Ecuador utilizando el modelo probabilístico logit: período 2005-2006 - Armijos Suarez, Hugo (2009)
The objective of this paper is to study the level of education acquired by a person and the determinants of that result. For this purpose, we analyze five categories: attend primary school, complete primary school, attend secondary school, complete secondary school, and attend to university. A Logit model is applied for each category in order to explain the occurrence probability for every event analyzed. The conclusion reached is that the socio-economic characteristics are significant determinants of education acquired by a person and have important effects over the probability of meeting the different educational levels.